Decadal changes in blood δ13C values, at-sea distribution, and weaning mass of southern elephant seals from Kerguelen Islands. Issue 1933 (19th August 2020) - Mestre, Julie; Authier, Matthieu; Cherel, Yves; Harcourt, Rob; McMahon, Clive R.; Hindell, Mark A.; Charrassin, Jean-Benoît; Guinet, Christophe
Abstract : Changes in the foraging environment and at-sea distribution of southern elephant seals from Kerguelen Islands were investigated over a decade (2004–2018) using tracking, weaning mass, and blood δ 13 C values. Females showed either a sub-Antarctic or an Antarctic foraging strategy, and no significant shift in their at-sea distribution was detected between 2004 and 2017. The proportion of females foraging in sub-Antarctic versus Antarctic habitats did not change over the 2006–2018 period. Pup weaning mass varied according to the foraging habitat of their mothers. The weaning mass of sub-Antarctic foraging mothers' pups decreased by 11.7 kg over the study period, but they were on average 5.8 kg heavier than pups from Antarctic foraging mothers. Pup blood δ 13 C values decreased by 1.1‰ over the study period regardless of their sex and the presumed foraging habitat of their mothers. Together, these results suggest an ecological change is occurring within the Indian sector of the Southern Ocean with possible consequences on the foraging performance of southern elephant seals. We hypothesize that this shift in δ 13 C is related to a change in primary production and/or in the composition of phytoplankton communities, but this requires further multidisciplinary investigations.